The role of older adults in congregational discernment: lessons about LGBTQ+ inclusion - Harris, Helen (Journal of religion, spirituality & aging, 2022)
The role of older adults in Christian congregations is frequently connected to both longevity in the church and financial resources to sustain the work. These two factors can be combined to create a conservative perspective, preservation of the past, and power to influence decisions about change. In a study of 21 congregations across three denominations, the researchers found that while many older adult participants would communicate a negative response to LGBTQ+ inclusion in churches, leadership, and sacraments including marriage, others were committed to and led change, often from a social justice perspective.